Numerical investigation on the flow field, temperature distribution and swirl in small-scale tangential firing furnace - Zainudin A.F.; Hasini H.; Fadhil S.S.A. (Asian Research Publishing Network, 2023)
This paper presents a numerical investigation of the flow and combustion behaviour in a small-scale tangential firing furnace to study the occurrence of flow and temperature deviation without the influence of upper furnace structures. Particular emphasis is given to the flue gas flow field, velocity, temperature distribution, and swirl intensity at different furnace elevations. The CFD simulation result shows that the swirl and velocity distribution are perfectly symmetrical along the furnace. The swirl diameter becomes larger as furnace height increases. Flow and temperature deviation, which normally occur in full-scale furnace were absent in this case. The swirl intensity was found to be highly influenced by the tangential velocity. These initial findings are useful in understanding the flow behaviour in the furnace and thus, find the root cause of flow and temperature deviation in the full-scale furnace. 2006-2017 Asian Research Publishing Network (ARPN).